Discernible Impact of Fashion‘s Online Shopping With Mobile - Augmented Reality (AR) Application on the Consumer‘s Perspective in Indonesia - Daniel Ilham; Deborah Simorangkir (Conference Series, 2020)
To see the impact of Augmented Reality (AR) technology in fashion’s online shopping on the consumer’s perspective in Indonesia, a quantitative survey was distributed online to Indonesia young generation which born between 1981 and 2000. Non-probability sampling was conducted in order to collect primary data by making use of convenience sampling. A total amount of 147 valid responses were collected which were analyzed by correlation, linear regression and multivariate analyses. The variables related to acceptance and behavior through Augmented Reality technology (TAM: perceived ease of use, perceived usefulness, perceived enjoyment; DTPB: perceived self-efficacy) were found to be significantly related to the perspective of purchase intention, continuance intention and referral intention by the Indonesia young generation. Augmented reality can be used as a tool to enhance the consumers’ perception of the offered product in the Indonesia young generation. Therefore, this study can recommend online retailers to introduce an augmented reality strategy in order to raise Indonesia young generation purchase-, continuance-, referral intention of shopping goods and therewith increase the sales numbers.